The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1007/s00415-003-1097-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a short outpatient rehabilitation treatment on disability of multiple sclerosis patients

Abstract: It is well known that neurorehabilitation can reduce disability or improve handicap of people with multiple sclerosis (MS). The aim of this study was to evaluate the effectiveness of a short period (6 weeks) of a tailored, individualised outpatient rehabilitation program in people with progressive MS. A randomised-controlled trial was undertaken in patients with primary and secondary progressive MS referred to the Centro Sclerosi Multipla of Catania. One hundred and eleven patients were assessed at baseline an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 25 publications
(34 reference statements)
3
55
0
3
Order By: Relevance
“…Patti et al observed carry-over of benefits on disability for a further six weeks after a short outpatient treatment, without changing on impairment [27]. In Solari et al study, physical rehabilitation determined improvement in disability detected by FIM motor domains and had a positive impact on mental components of HRQoL perception [25].…”
Section: Jmir Serious Games [33]mentioning
confidence: 98%
See 1 more Smart Citation
“…Patti et al observed carry-over of benefits on disability for a further six weeks after a short outpatient treatment, without changing on impairment [27]. In Solari et al study, physical rehabilitation determined improvement in disability detected by FIM motor domains and had a positive impact on mental components of HRQoL perception [25].…”
Section: Jmir Serious Games [33]mentioning
confidence: 98%
“…Inpatient setting was associated with a significant improvement in functional impairment [], disability [23], functional independence [25,38] and HRQoL [25,26]. Trials conducted in outpatient setting demonstrated effectiveness of rehabilitation in improvement of muscular strength [22], walking capacity [30], functional independence [27,38], HRQoL [22,24,26]. Home-based rehabilitation produced significant improvement in HRQoL [34, 82,83] Below, we report the conclusions of several systematic reviews which searched to assess the effectiveness of multidisciplinary rehabilitation in PwMS to explore rehabilitation approaches in different settings.…”
Section: Cognitive Rehabilitationmentioning
confidence: 99%
“…It was stated in a Cochrane review that consisted of 14 randomized controlled and controlled clinical trials that a multidisciplinary rehabilitation approach was at the "strong evidence" level for short-term gains in the level of activity and participation in MS patients (1). There are a limited number of investigations about MS rehabilitation in the literature (1,(4)(5)(6)(7)(8)(9). Therefore, in our study, we aimed to review the sociodemographic and clinical features of the MS patients who were hospitalized at our inpatient clinic and the rehabilitation methods applied and to shed light on the studies that would be conducted on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Functional independence and healthrelated quality of life (HRQoL) are among the outcome measures more investigated. Some studies showed as rehabilitation can improve the motor parameters of functional independence measures (FIM) in PwMS [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, four possible options of rehabilitation's setting are described in clinical practice: home-based therapy, outpatient ambulatory therapy, inpatient hospital-based therapy and outpatient hospital-based therapy [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%